2014
DOI: 10.4028/www.scientific.net/amm.660.674
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Flow Past a Solid Sphere at Moderate Reynolds Number

Abstract: The unsteady three dimensional flow simulation around sphere using numerical simulation computational fluid dynamic for moderate Reynolds Number between 20 ≤ Re ≤ 500 is presented. The aim of this work is to analyze the flow regimes around sphere and flow separation. Extensive comparisons were made between the present predicted results and available experimental and numerical investigations, and showed that they are in close agreement. The results show that the vortex shedding increases with the Reynolds numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
2
3
0
Order By: Relevance
“…It demonstrates that when the Reynolds number grows, flow separation happens earlier. These findings agree with past researchers [14,17]. This is because as the velocity rises, the flow has more difficulty attaching to the sphere.…”
Section: Fig 8 -Velocity Streamlines With Some References Pointsupporting
confidence: 93%
See 1 more Smart Citation
“…It demonstrates that when the Reynolds number grows, flow separation happens earlier. These findings agree with past researchers [14,17]. This is because as the velocity rises, the flow has more difficulty attaching to the sphere.…”
Section: Fig 8 -Velocity Streamlines With Some References Pointsupporting
confidence: 93%
“…When the flow in the boundary layer becomes turbulent, the drag coefficient lowers as the Reynolds number increases, allowing a separation point to travel further away from the rear body, lowering wake size and pressure drag magnitude. These findings are consistent with prior research, which found that the annotated drag coefficient falls as the Reynolds number increases [14,16].…”
Section: Drag Coefficientsupporting
confidence: 92%
“…Other studies conducted by Yin and Ong (2020), Constantinescu and Squires (2004), Sadikin et al (2014), andYen et al (2017) demonstrated that the flow past a solid sphere differs from the flow past a circular cylinder, especially in terms of vortex shedding in the wake flow behind the sphere. In the past, numerical analysis studies were performed in order to reach a comprehensive understanding of the flow past a simple body before applying the method to a more complex geometry.…”
Section: Introductionmentioning
confidence: 96%
“…In the literature [5,6], some summaries that the flow mechanisms in wake field were not the same in different Reynolds number intervals were given. Flow separation around a sphere occurs when the shear stress is zero [8]. The flow separation angle measured from the front stagnation point decreases with the increasing Reynolds number between 20 and 500.…”
Section: Introductionmentioning
confidence: 99%